Supervisi Akademik dan Manajemen Kelas terhadap Kualitas Mengajar Guru SMP Negeri Se-Kecamatan Prabumulih Timur - Hernasyahnova Hernasyahnova; Bukman Lian; Rohana Rohana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the academic supervision and classroom management on the teaching quality of teachers in State Junior High Schools in East Prabumulih District. This type of research is a quantitative research with a research design using an expost facto research research design. The sample in this study is the total of all teachers of State Junior High Schools in East Prabumulih District. which consists of 136 teachers. Data collection techniques using questionnaires. The data analysis technique uses quantitative descriptive analysis techniques, and multiple regression. The results of this study stated that 1) there was a significant influence of academic supervision on the quality of teacher teaching in State Junior High Schools in East Prabumulih District; 2) there is a significant influence of classroom management on the teaching quality of teachers in State Junior High Schools in East Prabumulih District: 3) there is a significant influence of academic supervision and classroom management together on the teaching quality of teachers in State Junior High Schools in East Prabumulih District. Keywords: Academic Supervision, Classroom Management, Teacher Teaching Quality